Role of Gd2O3 on structure rearrangement and elastic properties ZnO-Al2O3-B2O3-SiO2 glass system - Ismail, N.a.n.; Zaid, M.H.M.; Matori, K.A.; Fen, Y.W.; Cheong, W.M.; Loh, Z.W.; Shah, A.Z.; Hisam, R.; Azlan, M.N.; Iskandar, S.M. (Elsevier, 2023)
Zinc-alumino-borosilicate glass with gadolinium dopant (ZABS-Gd), (60-x)ZnO–5Al2O3–15B2O3–20SiO2:xGd2O3 where x = 0, 0.5, 1, 2, and 3 mol was synthesized via conventional fast cooling melt-quenching method. The differential scan calorimetry (DSC) findings showed that the glass transition temperature (Tg) had various thermal trends as the Gd3+ content rose. X-ray diffraction (XRD) analysis proves the absence of crystalline in the glass samples. With the increment of Gd3+ concentration, the ZABS-Gd glasses’ density climbs noticeably from 3.775 to 4.109 g/cm3 , and the molar volume likewise grows from 20.234 to 20.642 cm3 /mol. The values for experimental elastic moduli were attained from non-destructive ultrasonic measurement by using wave pulse-echo method, show an increasing trend from 4285.121 to 5482.091 ms− 1 for VL and 2296.538–3418.128 ms− 1 for VS. Following that, the experimental elastic moduli including shear modulus (G), Young’s modulus (E), bulk modulus (K), and Poisson’s ratio (σ) were contrasted to the elastic theoretical simulation computed by the Makishima-Mackenzie model.